The Effect of Different Solvents on Total Tannin Content of Cengkodok (Melastoma malabathricum) Leaf Extracts - Masriani Masriani; Khofifah Aditha Parawansa; Risya Sasri; Ajuk Sapar; Erlina Erlina; Ersando Ersando (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The use of synthetic dyes as color enhancers or generators has caused various environmental and health problems. Plant tannin biomordants offer an alternative solution to address these issues. The sample used in this study were Cengkodok (M. malabathricum) plants that grow wild in places that get enough sunlight such as shrubs. Phytochemical screening on various parts of the cengkodok plant revealed that the highest tannin content is found in the leaf. However, until now there has been no scientific evidence that presents differences in tannin levels in cengkodok leaf with various types of solvents. This study aims to determine the yield and total tannin content of cengkodok leaf extract obtained through maceration process using methanol, ethanol, and ethyl acetate solvents. The extract yield was determined by comparing the weight of the dry extract with the powdered cengkodok leaf material. The total tannin content was analyzed using UV-Vis spectroscopy at a wavelength of 755.8 nm with Folin-Ciocalteu reagent and sodium carbonate. Tannic acid was used as a reference. The research results showed that the yield values for Cengkodok leaf extracted with methanol, ethanol, and ethyl acetate were 5.05%, 4.72%, and 1.59%, respectively. The total tannin content of cengkodok leaf extracts with methanol, ethanol, and ethyl acetate solvents was 0.47%±0.04, 0.37%±0.01, and 0.19%±0.04, respectively. Based on this research, it can be concluded that methanol is the most effective solvent in extraction and determination of total tannin content of Cengkodok leaf extracts.